2008
DOI: 10.1158/1541-7786.mcr-07-2150
|View full text |Cite
|
Sign up to set email alerts
|

Association of HDM2 Transcript Levels with Age of Onset and Prognosis in Soft Tissue Sarcomas

Abstract: The p53 stress response is crucial for the prevention of tumor formation. The oncogene HDM2 is one of the key negative regulators of p53 and is a central node in the p53 pathway. P53 and HDM2 form an oscillating feedback loop. HDM2 expression is regulated by different promoters. To evaluate its clinical relevance, we determined the levels of HDM2 transcripts originating from the constitutive P1 and p53-sensitive P2 promoter in 133 soft tissue sarcomas and correlated the results with the age of diagnosis and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Another confirmatory study showed that the effect on patient survival of Mdm2/p53 cooverexpression was greater than the additive effects of each independently [67]. Additionally, high levels of Mdm2 mRNA expression are correlated with an earlier age of onset of soft-tissue sarcomas [60]. Altogether, these findings point to Mdm2 having p53-independent effects in the process of tumorigenesis.…”
Section: Mdm2 and Cancermentioning
confidence: 99%
“…Another confirmatory study showed that the effect on patient survival of Mdm2/p53 cooverexpression was greater than the additive effects of each independently [67]. Additionally, high levels of Mdm2 mRNA expression are correlated with an earlier age of onset of soft-tissue sarcomas [60]. Altogether, these findings point to Mdm2 having p53-independent effects in the process of tumorigenesis.…”
Section: Mdm2 and Cancermentioning
confidence: 99%
“…High levels of alternative mdm2 splicing are seen in tissue samples from ovarian and bladder carcinomas, some types of leukemia, breast carcinoma, soft tissue sarcoma, Hodgkin’s lymphoma, glioblastoma, rhabdomyosarcomas, liposarcomas, and lung carcinomas. 5,9,10,13,47-51 Mouse model information suggests that the tumor promoting capacity of Mdm2 does not require inhibition of wild-type p53. Exogenous expression of Mdm2-FL in mice was documented in 1998 to predispose the animals to sarcomas in a p53-independent manner.…”
Section: Alternative Splicing Of Mdm2: Increasing Mdm2 Proteome Divermentioning
confidence: 99%
“…Isolation of total RNA and cDNA synthesis were performed according to standard protocols as described previously [19]. The cDNA was amplified by automated real-time quantitative TaqMan™ assays for the wild type LGR5/GPR49 and GPR49Δ5 transcript variants and Hypoxanthin- guanine -phosphoribosyltransferase (HPRT) transcript using kits from Roboscreen (AJRoboscreen GmbH, Leipzig, Germany).…”
Section: Methodsmentioning
confidence: 99%